Couples Adjusting to Multimorbidity: A Dyadic Study on Disclosure and Adjustment Disorder Symptoms - Horn, Andrea B.; Boettcher, Victoria S.; Holzer, Barbara M.; Siebenhuener, Klarissa; Maercker, Andreas; Battegay, Edouard; Zimmerli, Lukas (Frontiers in Psychology, 2019)
Background Multimorbidity is challenging not only for the patient but also for the romantic partner. Strategies for interpersonal emotion regulation like disclosing to the partner are supposed to play a major role in the psychosocial adjustment to multimorbidity. Research has often focused on disease-related disclosure, even though disclosing thoughts and feelings related to mundane, everyday life occurrences might also play a role in coadjustment. The current dyadic study aimed at investigating the association between these two types of interpersonal regulation strategies and adjustment disorder symptoms, following the new ICD 11 criteria in multimorbid patients and their partners. Methods Shortly after being hospitalized due to an acute health crisis, N = 28 multimorbid patients (average age 70 years) and their partners filled in questionnaires on disclosure in the couple, adjustment disorder criteria of the ICD 11 (“preoccupation,” “failure to adapt”), and sleep problems. Results Both patients and their partners did show similarly high levels of preoccupation and failure to adapt indicating adjustment problems to the complex health situation. The adjustment symptoms of both partners correlated between r = 0.22 and 0.45. Regression based on Actor-Partner Interdependence-Models revealed that own mundane disclosure was related to less adjustment symptoms in the patients. Beyond that, a partner effect was observed, revealing a negative association between partners’ illness-related disclosure and the patients’ level of preoccupation. For the partners, mundane disclosure of the partner was associated with less preoccupation, failure to adapt, and reported sleep problems above and beyond own disclosure reports. Furthermore, there was an actor effect of disease-related disclosure on less sleep problems for the partners. Conclusion These results support an interpersonal view on adjustment processes to physical disease. Disclosure as a way of regulating the relationship and emotional responses might play a relevant role here, which seems to be different for patients and their partners. Further research is needed to shed more light on the differential role of disease-related and mundane everyday disclosure for psychosocial adjustment in couples confronted with health challenges.